2016
DOI: 10.1038/ncomms10859
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic capsule restructuring by the main pneumococcal autolysin LytA in response to the epithelium

Abstract: Bacterial pathogens produce complex carbohydrate capsules to protect against bactericidal immune molecules. Paradoxically, the pneumococcal capsule sensitizes the bacterium to antimicrobial peptides found on epithelial surfaces. Here we show that upon interaction with antimicrobial peptides, encapsulated pneumococci survive by removing capsule from the cell surface within minutes in a process dependent on the suicidal amidase autolysin LytA. In contrast to classical bacterial autolysis, during capsule shedding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 57 publications
11
83
0
Order By: Relevance
“…Cps A appears to act as a transcriptional activator of polysaccharide production but is not necessary for encapsulation 24. Unencapsulated pneumococcal strains evolve through either downregulation of the capsule or loss of the capsular biosynthesis locus 30. Non-typeable isolates of S. pneumoniae have been reported increasingly following vaccination and one earlier study found them to represent 28% of pneumococcal isolates, although the sample size of pneumococcal isolates was small (59 isolates) similar to that of our work 31.…”
Section: Discussionsupporting
confidence: 66%
“…Cps A appears to act as a transcriptional activator of polysaccharide production but is not necessary for encapsulation 24. Unencapsulated pneumococcal strains evolve through either downregulation of the capsule or loss of the capsular biosynthesis locus 30. Non-typeable isolates of S. pneumoniae have been reported increasingly following vaccination and one earlier study found them to represent 28% of pneumococcal isolates, although the sample size of pneumococcal isolates was small (59 isolates) similar to that of our work 31.…”
Section: Discussionsupporting
confidence: 66%
“…The central region of IgG-binding sites in M proteins appear to be contradictory to its role as an immune evasion mechanism, since a direct contact with the host's immunoglobulins is abrogated. However, capsule expression is a very dynamic process and can vary depending on environmental and stress conditions, such as nutrient availability or antibiotic treatments (Hammerschmidt et al, 2005; Willenborg et al, 2011; Haas and Grenier, 2016; Kietzman et al, 2016). Under nutrient-rich conditions, capsule expression is highly upregulated which is consistent with numerous studies characterizing the bacterial capsule as the main virulence factor of streptococci in the blood (Wu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, pneumococci markedly reduce capsule thickness when in close contact with epithelial cells and during the invasion process 123 . This process of capsule shedding has recently been shown to depend on the major pneumococcal autolysin LytA and is triggered by exposure to cationic antimicrobial peptides that are released by the host cells 124 .…”
Section: Invasive Pneumococcal Diseasementioning
confidence: 99%